Mindfulness Interventions for Disaster Resilience in Southeast Asia - Panting, Adriana (Archīum Ateneo, 2020)
This chapter summarizes the literature on mindfulness and its impact of postdisaster response. Although the use of mindfulness is still in its infancy in Southeast Asia (SEA), initial studies suggest it has potential as a means to address survivors’ posttrauma symptoms. Given cultural nuances such as a discomfort in emotional expression and shame, mindfulness is non-intrusive and encourages non-judgmental acceptance. Mindfulness has been used in group settings which is congruent with the region’s collectivist orientation. In addition, given the importance of spirituality, we suggest that mindfulness may be an inclusive approach that is familiar and acceptable to SEA survivors.